2019
DOI: 10.1037/ocp0000154
|View full text |Cite
|
Sign up to set email alerts
|

Why do individuals suffer during unemployment? Analyzing the role of deprived psychological needs in a six-wave longitudinal study.

Abstract: This 6-wave study addresses the psychological meaning of employment by examining the psychological need mechanisms predicting psychological distress during unemployment and reemployment. According to the deprivation model, unemployed people suffer, as unemployment deprives them of the latent functions of employment (i.e., time structure, social contact, status, activity, and collective purpose), which reflect psychological needs that are important for mental health. We tested whether the latent functions of em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 79 publications
1
30
0
Order By: Relevance
“…Lower socioeconomic status (SES) is associated with high psychological distress, and lower subjective social status is related to poor mental health. Poverty and unemployment play an important role in distress ( Zechmann and Paul, 2019 ). Some studies have indicated that traditional SES variables, such as household income, can directly affect psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…Lower socioeconomic status (SES) is associated with high psychological distress, and lower subjective social status is related to poor mental health. Poverty and unemployment play an important role in distress ( Zechmann and Paul, 2019 ). Some studies have indicated that traditional SES variables, such as household income, can directly affect psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…Although unemployment is not synonymous with job loss, an obvious career shock, the latter typically leads to the former, as for instance only 1% of the unemployed in Finland are estimated to be voluntarily unemployed [44]. In addition to its manifest functions (financial situation), employment has several latent functions; for example, social contacts, time structure, status, activity, collective purpose, and the psychological need of competence [45]. A lack of these functions has been found to mediate the relationship between unemployment and distress, and re-employment in turn has predicted gains in these functions, which in turn have led to reduction in distress [45].…”
Section: Work Engagement and Sustainable Careersmentioning
confidence: 99%
“…In addition to its manifest functions (financial situation), employment has several latent functions; for example, social contacts, time structure, status, activity, collective purpose, and the psychological need of competence [45]. A lack of these functions has been found to mediate the relationship between unemployment and distress, and re-employment in turn has predicted gains in these functions, which in turn have led to reduction in distress [45]. Therefore, unemployment can be considered a specific kind of career shock.…”
Section: Work Engagement and Sustainable Careersmentioning
confidence: 99%
“…As mentioned in Section 2, Jahoda (1981) argues that employment is psychologically beneficial because it gives a time structure to the day, allows people to get in contact with others outside the family, forces people to be active, links people with broader goals, and defines personal status and identity. To understand the relative importance of each of these channels, one would have to empirically separate and quantify each of these five latent benefits of work, or at least subgroups of them (for an example, see Zechmann and Paul 2019). To that end, it is useful to differentiate between the first three latent benefits and the latter two.…”
Section: Identity Utilitymentioning
confidence: 99%